A Field Survey To Investigate The Flora And Fauna of Dhauladhar Nature Park in North-Western Himalayan Region of India - Neeraj, Sharma Kumar (Journal of Tropical Life Science, 2015)
Taxonomic studies on wildlife biodiversity has always been very fascinating along with the great purpose of providing valuable information on their present status concerning species number and future course of action required for their conservation. A study regarding survey of flora and fauna was carried out at Dhauladhar Natureâ€™s Park of Gopalpur in district Kangra of Himachal Pradesh during the month of April 2015. The present study has revealed the presence of 09 mammals, 02 reptilia, 05 pheasants and 04 other birds belonging to 12 families along with 44 plant species belonging to 28 families. Further it is suggested that provisions for Himalayan snakes and butterflies, the other two imperative Himalayan fauna be created as soon as possible so that natureâ€™s park can fulfill its Â true purpose of conservation of Himalayan wild animals in real sense.